Problematika Pastoral Kaum Muda: Starategi Pastoral Berbasis Digital dalam Pastoral Kaum Muda - Theresiani Bheka; Intansakti Pius X (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Pastoral issues in dealing with young people are a complex challenge in today's digital age. Young people often have different needs and ways of communicating, thus requiring a pastoral approach that fits the digital context. Digital-based pastoral strategies are key in understanding and touching the hearts of young people and guiding them in faith and spiritual life. This study aims to analyze the pastoral issues faced by young people and formulate effective digital-based pastoral strategies to address these challenges. Through a qualitative approach and literature study, this research highlights the importance of pastoral adaptation to the development of digital technology in developing relevant and meaningful relationships with young people. The results of this study are expected to contribute to enhancing the pastoral effectiveness of the church in responding to and guiding young people in the digital era, therefore the author prepares a digital pastoral strategy for young people.